Модель виявлення та класифікації цілей для квадрокоптеру DJI MAVIC 3 - Бутирін, І. С. (ХНУРЕ, 2024)
This work is intended to study and create a machine learning model, namely in the field of computer vision, which should detect and classify targets. This is a field of artificial intelligence that deals with the development of algorithms and technologies that allow computers to interpret and analyze images and videos. Developing a solution requires a large amount of data, since the accuracy of the model depends on it.
Keywords: квадрокоптер; класифікація цілей для квадрокоптера